Faktor-Faktor Penyebab Rendahnya Minat Petani di Kabupaten Pamekasan untuk Membudidayakan Jagung Hibrida: Factors Influencing Low Farmer Interest in Cultivating Hybrid Corn in Pamekasan Regency - Layalie, M Syahiral; Sugiarti, Teti; Pawana, Gita (Journal of Integrated Agribusiness, 2024)
This study aims to analyze and describe the internal factors among farmers, such as capital ownership, land area, farmer knowledge, the role of women farmers, and farming objectives, and how these affect the low interest in cultivating hybrid corn. Additionally, it examines external factors including production costs, cultivation techniques, availability and affordability of quality seeds, intensity of pest attacks, irrigation water needs, harvest period, product quality (color and taste), product shelf life, market opportunities, and selling price of hybrid corn. The findings of this study can serve as a basis for formulating future government or private sector programs to boost corn production in Pamekasan Regency, taking into account specific local conditions to support community welfare.